STRATEGI PROMOSI MEDIA SOSIAL, REPUTASI DEVELOPER DAN INOVASI PRODUK DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PADA PROPERTI LAVISH HILLS RESIDENCE BATAM DEVELOPER CIPUTRA GRUP - Ruslan, Ruslan; Karnawati, Tin Agustina; Handoko, Yunus (Jurnal Manajemen dan Profesional, 2023)
The aim of this study is to scientifically determine what variables are considered by consumers before deciding to make a purchase at Lavish Hills Residence Batam by Ciputra Group. The variables used in this study include: social media promotion, developer image, and product innovation. Quantitative research is the method employed. The population in this study amounted to 148 consumers. Simple random sampling is a sampling method used in this study, and through the use of Slovin formula has collected samples used as many as 108 respondents. In this work, multiple linear regression analysis approaches were implemented as the analytical strategy. According to the study's findings, product innovation and developer image had a positive and significant influence on consumers' decisions to purchase a property at Lavish Hills Residence Batam. However, social media promotion had a positive but not statistically significant impact.